The Safety and Tolerability of 5-Aminolevulinic Acid Phosphate with Sodium Ferrous Citrate in Patients with Type 2 Diabetes Mellitus in Bahrain - Al-Saber, Feryal (J Diabetes Res, 2016)
Type 2 diabetes mellitus is prevalent especially in Gulf countries and poses serious long-term risks to patients. A multifaceted treatment approach can include nutritional supplements with antioxidant properties such as 5-aminolevulinic acid (5-ALA) with sodium ferrous citrate (SFC). This prospective, randomized, single-blind, placebo-controlled, dose escalating pilot clinical trial assessed the safety of 5-ALA with SFC at doses up to 200 mg 5-ALA/229.42 mg SFC per day in patients living in Bahrain with type 2 diabetes mellitus that was uncontrolled despite the use of one or more antidiabetic drugs. Fifty-three patients (n = 53) from 3 sites at one center were enrolled by Dr. Feryal (Site #01), Dr. Hesham (Site #02), and Dr. Waleed (Site #03) (n = 35, 5-ALA-SFC; n = 18, placebo). There was no significant difference in incidence of adverse events reported, and the most frequent events reported were gastrointestinal in nature, consistent with the known safety profile of 5-ALA in patients with diabetes. No significant changes in laboratory values and no difference in hypoglycemia between patients receiving 5-ALA and placebo were noted. Overall, the current results support that use of 5-ALA-SFC up to 200 mg per day taken as 2 divided doses is safe in patients taking concomitant oral antidiabetic medications and may offer benefits in the diabetic population. This trial is registered with ClinicalTrials.gov NCT02481141.